4(c-5)=2(c+11)

Simple and best practice solution for 4(c-5)=2(c+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(c-5)=2(c+11) equation:



4(c-5)=2(c+11)
We move all terms to the left:
4(c-5)-(2(c+11))=0
We multiply parentheses
4c-(2(c+11))-20=0
We calculate terms in parentheses: -(2(c+11)), so:
2(c+11)
We multiply parentheses
2c+22
Back to the equation:
-(2c+22)
We get rid of parentheses
4c-2c-22-20=0
We add all the numbers together, and all the variables
2c-42=0
We move all terms containing c to the left, all other terms to the right
2c=42
c=42/2
c=21

See similar equations:

| 2(2x+2)=104 | | 6x-3+4x-3=80 | | 2x-3/4-x-3/3=x+5/8 | | i/2-3=4 | | 8x=10=18 | | 9g+3=10g | | 6x+3=9x+0 | | 8+7a=50 | | 5t+6=5t-3 | | x^2−x=3x | | (-3)=7x-4 | | -6-12p=4p-3 | | m1=50+93 | | 8x-1=4(x+1)-1 | | -3/4x+7=-2 | | 2x+5=6(2x+1) | | -16+5m=-6(-6+8m+3) | | D=9/2(m-53) | | 15+3m-9=4(m-3) | | 5(x+6)=30-3x | | -2x+114=180 | | -15x+3(x-3)+9x=8x-64 | | m1+42=112 | | 20=6-7h | | 120-(3x=60) | | 3x+2x=7+2 | | 2x+8x-12=-9x+148 | | 40-4x=2 | | -16+5m=-6(-6+8m+3 | | 6+2(3a+4)=8 | | -8w-10=-6(w+3) | | +(3)/(5)=(z)/(5) |

Equations solver categories